Enhancing gastric cancer conventional chemotherapy effects by triple angiokinase inhibitor nintedanib in preclinical models - Awasthi, Niranjan; Schwarz, Margaret A.; Kaurich, Quinn; Zhang, Changhua; Hilberg, Frank; Schwarz, Roderich E. (Frontiers in Oncology, 2023)
Background Gastric adenocarcinoma (GAC) is the fourth leading cause of cancer death worldwide. Systemic chemotherapy is a preferred treatment option for advanced and recurrent GAC, but response rates and survival prolongation remain limited. Tumor angiogenesis plays a critical role in GAC growth, invasion and metastasis. We investigated the antitumor efficacy of nintedanib, a potent triple angiokinase inhibitor for VEGFR-1/2/3, PDGFR-α/β and FGFR-1/2/3, alone or in combination with chemotherapy, in preclinical models of GAC. Methods Animal survival studies were performed in peritoneal dissemination xenografts in NOD/SCID mice using human GAC cell lines MKN-45 and KATO-III. Tumor growth inhibition studies were performed in subcutaneous xenografts in NOD/SCID mice using human GAC cell lines MKN-45 and SNU-5. The mechanistic evaluation involved Immunohistochemistry analyses in tumor tissues obtained from subcutaneous xenografts. In vitro cell viability assays were performed using a colorimetric WST-1 reagent. Results In MKN-45 GAC cell-derived peritoneal dissemination xenografts, animal survival was improved by nintedanib (33%), docetaxel (100%) and irinotecan (181%), while oxaliplatin, 5-FU and epirubicin had no effect. The addition of nintedanib to docetaxel (157%) or irinotecan (214%) led to a further extension in animal survival. In KATO-III GAC cell-derived xenografts carrying FGFR2 gene amplification, nintedanib extended survival by 209%. Again, the addition of nintedanib further enhanced the animal survival benefits of docetaxel (273%) and irinotecan (332%). In MKN-45 subcutaneous xenografts, nintedanib, epirubicin, docetaxel and irinotecan reduced tumor growth (range: 68-87%), while 5-FU and oxaliplatin had a smaller effect (40%). Nintedanib addition to all chemotherapeutics demonstrated a further reduction in tumor growth. Subcutaneous tumor analysis revealed that nintedanib attenuated tumor cell proliferation, reduced tumor vasculature and increased tumor cell death. Conclusion Nintedanib showed notable antitumor efficacy and significantly improved taxane or irinotecan chemotherapy responses. These findings indicate that nintedanib, alone and in combination with a taxane or irinotecan, has the potential for improving clinical GAC therapy.